Innovation Diffuse “E-DELJIT” System: A New Concept in Reducing the Impact of Supply Networks Disruption - Santhirasegaran Nadarajan; Mohd Kamarul Irwan Abdul Rahim; Adam Mohd Saifudin (International Journal of Supply Chain Management, 2019)
This article seek to provide research opportunities in supply chain networks. For manufacturing industries, materials supply is an essential input to the production process for a sustainability value creation for firms and stakeholders. However, due to several reasons have caused issues to material short supplies in the production process that caused additional cost leading to a negative impact to firm operating performance. The purpose of this study to address the current phenomena of materials stoppage or short supply that affects the production process ultimately creating a possible loss to firm from the delayed time in the production process and supply of finished goods to customers. This has been ongoing crisis felt by manufacturers that require immediate attention particularly by those charged of organizational governance from operational to strategic level management of firm operation along the line of supply chain process. This article mainly to focus on the factors contributing to materials shortages or short supply in the production process in manufacturing industries.Â  This material/inventory problem has not been discussed and lack of investigation done so far, well this article will bring out the important issues related to materials shortage that require further attention especially academician, researchers and managers. Therefore, the operation challenging issues pertaining to parts/ material shortage should be known through this paper. Further, the contribution outcome of this paper, addresses the critical issues related to production line stoppage that mainly caused by materials shortages based on the authorâ€™s more than twenty years working experience dealing with materials shortages issues in the electronic electrical base manufacturing. This article will be practical guide to those manufacturing industries facing poor supply of parts issues that add additional costs to firms which influence the operating profit/ performance. This article seeks to spur inventory operations research and providing examples and cases of deductive approach believe to be helpful and nurturing particularly the middle level management to make effective decision and also the academicians to further findings towards constructive and sustainability solution to firm operationÂ